2012
DOI: 10.1007/s13337-012-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Foot-and-Mouth Disease Virus Non-Structural Protein, 3D in Insect Cells and its Application in Detection of Anti-FMDV Antibodies

Abstract: Non-structural proteins (NSPs) based diagnostics are useful for large-scale sero-surveillance of foot-andmouth disease (FMD) and to monitor viral activity as a follow up to the vaccination campaign in FMD endemic countries like India which aim at disease control through vaccination. These diagnostics are also handy in the serology of import/export of cloven-footed animals. In the present study, non-structural protein RNA polymerase (3D gene) of FMD virus (FMDV) was expressed using baculovirus expression system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…Comparing between cardiac biomarkers had been documented that, after cardiac injury started, serum CK-MB concentration will increase faster and peaked within 24 hour and serum LDH within 48 -72 hours ,whereas cardiac troponin starts to increase during the 3-4 hours and were peaked at the 12 hours, those results were confirm by the results of the present study and agreed with others (34), therefore, it were reported that CK-MB levels, as a marker of myocardial cell damage, are often increase in its range during the very early stage of myocarditis (17). Hereby the current study can be suggested that the stage of the disease is very early.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparing between cardiac biomarkers had been documented that, after cardiac injury started, serum CK-MB concentration will increase faster and peaked within 24 hour and serum LDH within 48 -72 hours ,whereas cardiac troponin starts to increase during the 3-4 hours and were peaked at the 12 hours, those results were confirm by the results of the present study and agreed with others (34), therefore, it were reported that CK-MB levels, as a marker of myocardial cell damage, are often increase in its range during the very early stage of myocarditis (17). Hereby the current study can be suggested that the stage of the disease is very early.…”
Section: Discussionsupporting
confidence: 93%
“…The dams of the calves in the current study have no previous history of vaccination against FMD and were showed the classical signs of the disease, therefore, the primarily or a presumptive diagnosis of myocarditis due to the disease was made although the diseased calves had no vesicular and erosive lesions of FMD, whereby both myocarditis and FMD were confirmed firstly based on serological diagnosis of the non-structural proteins (NSP) ELISA test, hereby the use of (NSP) allows detection of antibodies against FMD virus in infected non vaccinated animals, as the use of (NSP) allows detection of antibodies that are mostly only produced during infection where virus has replicated, furthermore, the possibility that some animals will show no clinical signs of disease but will have had replication of virus, such animals may carry the FMD virus and possibly represent a threat to other animals (16,17). Moreover, confirmation of FMD myocarditis could also base on the macroscopic and microscopic features of died or slaughtered animals subjected to post mortem examination, since results of this study were indicated necrotic myocarditis with pale foci and a zone of hyperemia on the papillary and ventricular cardiac muscles, furthermore, though, histopathological examinations there were severe inflammatory cells infiltration in the interstitial of myocardial fibers, accordingly a coagulative necrosis of myocardial fibers and marked area of hyalinization were also confirm the disease, same results were also described and confirmed by (4,18).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that sera from animals vaccinated using currently licensed vaccines in India appear to elicit an NSP antibody response after repeated immunizations [17,18]. Some vaccines, though produced a strong antibody response to structural proteins (data not shown), they apparently were not completely purified from NSP contaminants as evident in this study.…”
Section: Discussionmentioning
confidence: 46%
“…Studies on the involvement of these proteins and elements provided important insights into the molecular mechanism of virus-induced diseases. Nearly all NSPs and NCEs of FMDV are under investigation for their involvement in either virus detection or potential anti-viral strategy development [ 197 205 ], although progress is slow. FMDV is unique among the picornavirus family because of its long 5ʹ-UTR, three copies of 3B protein and short 2A protein lacking any protease motifs.…”
Section: Conclusion and Perspectivementioning
confidence: 99%